(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
This work aims to evaluate the feasibility of castor bean residue as the precursor of activated carbon by metal chloride salts as activating agent. ZnCl2, NaCl and KCl were used to activate the castor bean residue and the performance was investigated by adsorption of methylene blue and its correlation with the specific surface area. ZnCl2-activated castor bean cake with had the best adsorption result with maximum capacity of 213 mg/g and specific surface area of 643 m2/g. The adsorption of methylene blue for all metals chloride-activated castor bean residue followed Langmuir isotherm which suggests monolayer adsorption onto the homogeneous surface.